Upper border of anal transitional zone: a new landmark for endoscopic internal hemorrhoid therapy - Jingyao Li; Huiyan Li; Hao Xu; Jing Dong; Tiantian Guo; Hongjiao Yao; Qi Yang (Frontiers in Medicine, 2026)
Background and aim Endoscopic therapies are important approaches for managing internal hemorrhoids. This study assessed the feasibility of endoscopic examination of the upper border of anal transitional zone (ATZ) and its clinical utility and underlying anatomical basis as a landmark for internal hemorrhoid. Methods Mucosal demarcation line (MDL) and the dentate line were identified and measured in 207 adults using white-light and narrow band imaging (NBI) endoscopy, with three biopsies for histologic confirmation. Five anorectal specimens were examined employing hematoxylin and eosin staining and immunohistochemistry for S100 and PGP9.5 to evaluate hemorrhoidal cushion position and nerve distribution. Ninety-three patients undergoing sclerotherapy or rubber band ligation (RBL) with MDL as reference were followed using symptom questionnaires and complication assessments. Results (1) A distinct MDL was identified above the dentate line in 69.08% of participants under white light imaging, increasing to 96.14% under NBI ( p < 0.001), located 8.18 ± 2.96 mm above the dentate line. (2) Histologically, MDL represented the upper border of ATZ based on epithelial transition; hemorrhoidal cushions extended 6.81 ± 4.21 mm above MDL. (3) PGP9.5-positive intraepithelial free nerve endings were present within ATZ at a lower area ratio than the non-keratinized ( p = 0.038) and keratinized mucosa below the dentate line ( p < 0.001) and were absent in the rectal mucosa. (4) Using MDL (the upper border of ATZ) as reference, six-month effective rates were 91.80% for sclerotherapy and 93.75% for RBL, with significant improvement in anal discomforts and defecatory disorders. Postoperative discomfort occurred in 6.56 and 18.75% of patients, respectively, without major complications. Conclusion The upper border of ATZ can serve as a reliable endoscopic landmark for safe and effective treatment of internal hemorrhoid therapy, likely due to its anatomical relationship with the hemorrhoidal cushions and preservation of the ATZ.